The effect of off farm employment on agricultural production and productivity: evidence from gurage zone of southern Ethiopia - Nasir, M.; Kotu, Bekele Hundie (2014)
Theoretically there are two possible impacts of off-farm employment on agricultural production and productivity. On the one hand, they can enhance farm production by providing the finance needed for farm inputs and technologies and, on the other hand, off-farm activities may have a detrimental effect on farm output by competing farming for labor. The aim of this study is to explore the effect of off-farm employment participation of farm households on agricultural crop output yield and productivity. The data used for this study is collected from four rural kebeles of farm households with the total sample size of 221, and individual household head was selected by applying a multistage sampling technique. Sub districts were selected purposively based on their distance from the nearby town (Wolkite) as well as the type of crops produced, while households were selected randomly from a stratified sample frame. We used OLS and Tobit regressions to analyze the data. The results show that households’ engagement in off-farm activities is inversely related to crop production and, to some extent, to land productivity implying that the rural non-farm economy competes with agriculture for labor and that marginal productivity of labor in agriculture is positive.Theoretically there are two possible impacts of off-farm employment on agricultural production and productivity. On the one hand, they can enhance farm production by providing the finance needed for farm inputs and technologies and, on the other hand, off-farm activities may have a detrimental effect on farm output by competing farming for labor. The aim of this study is to explore the effect of off-farm employment participation of farm households on agricultural crop output yield and productivity. The data used for this study is collected from four rural kebeles of farm households with the total sample size of 221, and individual household head was selected by applying a multistage sampling technique. Sub districts were selected purposively based on their distance from the nearby town (Wolkite) as well as the type of crops produced, while households were selected randomly from a stratified sample frame. We used OLS and Tobit regressions to analyze the data. The results show that households’ engagement in off-farm activities is inversely related to crop production and, to some extent, to land productivity implying that the rural non-farm economy competes with agriculture for labor and that marginal productivity of labor in agriculture is positive.Theoretically there are two possible impacts of off-farm employment on agricultural production and productivity. On the one hand, they can enhance farm production by providing the finance needed for farm inputs and technologies and, on the other hand, off-farm activities may have a detrimental effect on farm output by competing farming for labor. The aim of this study is to explore the effect of off-farm employment participation of farm households on agricultural crop output yield and productivity. The data used for this study is collected from four rural kebeles of farm households with the total sample size of 221, and individual household head was selected by applying a multistage sampling technique. Sub districts were selected purposively based on their distance from the nearby town (Wolkite) as well as the type of crops produced, while households were selected randomly from a stratified sample frame. We used OLS and Tobit regressions to analyze the data. The results show that households’ engagement in off-farm activities is inversely related to crop production and, to some extent, to land productivity implying that the rural non-farm economy competes with agriculture for labor and that marginal productivity of labor in agriculture is positive.